PENGEMBANGAN MODEL PERMAINAN SEPAK BOLA GAWANG SKOR DALAM PENJASORKES BAGI SISWA KELAS V SEKOLAH DASAR NEGERI 5 TUBANAN KECAMATAN KEMBANG KABUPATEN JEPARA 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This  study  aims  to  develop  and  produce  a  model  of  learning  through  play  foot-ballgame goal scoring for elementary  school.  This  study is a research method that refers tothe  development  of  models  of  Borg  &  Gall  development  that  has  been  modified,namely:  (1)  a  preliminary  investigation  and  collection  of  information.  (2)  Developinitial  product  form.  (3)  Evaluation.  (4)  Revised  first  product.  (5)  field  t rial  (34students).  (6)  Revised  final  product.  (7)  The  final  result  by  the  field  test  revision.  Thedata  was  collected  using  a  questionnaire  derived  from  expert  evaluation,  small  grouptesting,  and  field  trials.  Data  in  the  form  of  the  assessment  of  t he  quality  of  products,suggestions  for  improvement  of  the  product,  and  the  results  of  the  ques-tionnaires  bystudents. The data analysis technique used is descriptive percentage to reveal aspects ofpsychomotor,  cognitive,  and  affective  student  after  using  the  product.  From  the  testresults  obtained  by  the  expert  evaluation  data,  expert  penjas  80%  (good),  80%  learningexpert s  (good),  a  small  test  group  80%  (good),  and  field  trials  80%  (good).  From  theavailable  data  it  can  be  concluded  that  the  model  of  learning  through  play  footballgoalkeeper  scores  can  be  used  for  st udents  of  classes  V  SD  Negeri  5  Tubanan  Jeparaacceptable because students and produce learning.